Interstellar computation their challenges and approaches in interplanetary cloud systems and data transmission - Jawad Abu-Alshaeer, Mahmood; Salim Jamil, Abeer; Jabbar Hussein, Mohammed; Omar Alo, Salam; Waleed Taha, Sarmad; Khlaponina, Anastasiia (Edelweiss Applied Science and Technology, 2024)
With the advancement of human civilisation beyond the confines of Earth's atmosphere, there has been an increasing need for efficient data processing and transmission in extraterrestrial environments. The article explores innovative strategies for resolving intricate computational challenges encountered in the context of interplanetary distances. The purpose of this study is to investigate the impact of issues such as latency, data corruption, and power consumption on classical computing paradigms in space. We examine the concept of "interplanetary cloud systems", which use distributed computation and data storage to tackle these issues. The article also covers advanced techniques for sending data, including communication systems using quantum entanglement and deep space networks. The article integrates the disciplines of astronomy, computer science, and space exploration to provide a holistic perspective on the issue. It is crucial to emphasise that the implementation of fault-tolerant systems, adaptive algorithms, and robust networking protocols is essential for the success of extrasolar computing programs. The article thoroughly explores the potential and risks that arise when space travel, astronomy, and computer science intersect. We explore the potential future of interplanetary data processing and communication technologies via the examination of fault tolerance, adaptive algorithms, and resilient networking. The importance of resolving computational issues in space increases as humanity extends its presence in the cosmos. The study results have significant ramifications for the development of forthcoming technology enabling interplanetary data transfer, hence facilitating human colonisation and scientific exploration beyond Earth.